2017
DOI: 10.3892/etm.2017.4647
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin protects against acute renal injury by suppressing JAK2/STAT3 pathway in severe acute pancreatitis in rats

Abstract: Abstract. The aim of the present study was to investigate the effect of curcumin on acute renal injury in a rat model of severe acute pancreatitis (SAP). A SAP model with acute kidney injury was established in rats by retrograde injection of 5% sodium taurocholate into the pancreatic duct. The serum amylase, creatinine (Cr) and blood urea nitrogen (BUN) levels in rats were measured. Hematoxylin and eosin staining was used to assess pancreatic and renal histological changes. Serum tumor necrosis factor (TNF)-α … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 32 publications
2
24
0
Order By: Relevance
“…Further, it is also involved in the modulation of aberrant epigenetics mechanisms and the expression of noncoding RNA [20]. Interestingly, a number of studies have shown that curcumin exerts its pharmacological action by targeting JAK/STAT3 signaling [22][23][24]. Anticancer drugs, such as cisplatin, that are used in chemotherapy (one of the therapeutic options used by clinicians) have been found to be associated with various critical complications, including drug resistance in papillary thyroid cancer (PTC) patients [11], and the available literature has shown that a number of natural products, including curcumin, have shown synergistic action with anticancer drugs [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Further, it is also involved in the modulation of aberrant epigenetics mechanisms and the expression of noncoding RNA [20]. Interestingly, a number of studies have shown that curcumin exerts its pharmacological action by targeting JAK/STAT3 signaling [22][23][24]. Anticancer drugs, such as cisplatin, that are used in chemotherapy (one of the therapeutic options used by clinicians) have been found to be associated with various critical complications, including drug resistance in papillary thyroid cancer (PTC) patients [11], and the available literature has shown that a number of natural products, including curcumin, have shown synergistic action with anticancer drugs [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that curcumin can reducing levels of proinflammatory cytokines, including interleukins (IL) and tumor necrosis factors (TNF) in several inflammation disorders such as bacterial infection and autoimmune arthritis [ 6 ]. Moreover, several previous studies suggested the protective effects of curcumin in animal models of SAP [ 7 ]. However, these studies did not describe the specific molecular mechanisms involved.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the enrichment analysis was innovatively used for the target identification since the enriched proteins often played similar and important biological roles in the biological process, and were likely to be the targets of the bioactive molecule. For example, the activation of JAK2 and STAT3 induced the expression of TNF-α and IL-6 in acute renal injury, while curcumin protected against the acute renal injury by distinctly inhibiting the activation of JAK2 and STAT3 in the JAK2/STAT3 pathway [ 47 ]. As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%